Environmentally induced phenotypic variation in wild yellow-bellied marmots (2015)
Phenotypic plasticity, the ability of an individual to modify its phenotype according to the conditions it experiences, is a source of between-individual variation and a mechanism by which individuals can cope with environmental change. Plasticity is expected to evolve in response to environmental heterogeneity, such as seasonality and year-to-year variation. We aimed to characterize patterns of phenotypic change in morphological (body mass), life-history (reproductive success and litter size), and social (embeddedness) traits of female yellow-bellied marmots (Marmota flaviventris) in response to climatic and social variation. We used data collected over 36 years on a population of yellow-bellied marmots studied in Colorado. We used mixed effect models to explore phenotypically plastic responses and tested for individual variation in mean trait values (i.e., intercept) and in plasticity (i.e., slope). All examined traits were plastic, and the population’s average plastic response often differed between spatially distinct colonies that varied systematically in timing of snowmelt, among age classes, and between females with different previous reproductive experiences. Moreover, we showed individual differences in June mass and pup mass plasticity. We suggest that plasticity plays a key role buffering the effects of continuous changes in environmental conditions.